Thismia papillata (Thismiaceae), a new species from northern Vietnam - Nuraliev, Maxim S.; Yudina, Sophia V.; Dac, Le Xuan; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P.; Semenyuk, Irina I. (Phytotaxa, 2024)
Thismia papillata, a new species of Thismiaceae, is described and illustrated. The species was discovered in 2023 in Thanh Hoa Province, northern Vietnam. The new species is readily distinguishable from most of its congeners by the presence of appendages of outer and inner tepals, inner tepals fused into a mitre, absence of a wing-like appendage of supraconnective and absence of interstaminal glands. Thismia papillata is similar to T. abei, T. taiwanensis and T. tuberculata, differing mainly in prominently papillate outer hypanthium surface, appendages of the outer tepals up to 15 mm long, appendages of the inner tepals up to 9 mm long, and column-like placentas. Gaps in understanding of interactions between the inner tepals in Thismia are highlighted that are related to the postgenital tepal fusion and tepal aestivation. Similar uncertainties in determination of fusion between the stamens are also uncovered.